Quantitative Economic Evaluation of Zakah-Poverty Nexus in Kano State, Nigeria - Mustafa, Daud; Baita, Abubakar Jamilu; Adhama, Hussaina Datijjo (International Journal of Islamic Economics and Finance (IJIEF), 2020)
Nigeria is the largest economy in Africa and yet, a poverty-ridden oil-producing country. Thus, poverty remains a persistent macroeconomic challenge in Nigeria with devastating consequences, especially in the Muslim populated states like Kano. Surprisingly, Kano state, which is the most populated state in Nigeria with more than 15 million people, is one of the 14 most poverty-ridden states in Nigeria, despite the practice of Zakah institution (ZI). Therefore, this study empirically evaluates the revenue base and impacts of ZI on poverty alleviation in Kano state. Hence, 1,230 copies of questionnaires were administered and seven high profile Zakah payers were interviewed. Meanwhile, the data analysis was accomplished using descriptive statistics, correlation, and regression techniques, among others. The major findings indicate that the enormous revenue base of ZI for poverty alleviation exists, because of the significant Zakah payment by high ability Zakah payers. Similarly, ZI positively impacts on poverty alleviation. All in all, the findings lend credence to the Zakah-effectiveness hypothesis. Hence, this study recommends that Kano state government should exemplify more accountability and transparency in Zakah management. Moreover, a Ministry of Zakah and Hubusi Affairs should be established with the mandates of poverty alleviation and economic empowerment in the state.